Crop rotations sustain cereal yields under a changing climate. (23rd November 2020) - Marini, Lorenzo; St-Martin, Audrey; Vico, Giulia; Baldoni, Guido; Berti, Antonio; Blecharczyk, Andrzej; Malecka-Jankowiak, Irena; Morari, Francesco; Sawinska, Zuzanna; Bommarco, Riccardo
Abstract: Agriculture is facing the complex challenge of satisfying increasing food demands, despite the current and projected negative impacts of climate change on yields. Increasing crop diversity at a national scale has been suggested as an adaptive measure to better cope with negative climate impacts such as increasing temperatures and drought, but there is little evidence to support this hypothesis at the field scale. Using seven long-term experiments across a wide latitudinal gradient in Europe, we showed that growing multiple crop species in a rotation always provided higher yields for both winter and spring cereals (average +860 and +390 kg ha −1 per year, respectively) compared with a continuous monoculture. In particular, yield gains in diverse rotations were higher in years with high temperatures and scant precipitations, i.e. conditions expected to become more frequent in the future, rendering up to c. 1000 kg ha −1 per year compared to monocultures. Winter cereals yielded more in diverse rotations immediately after initiation of the experiment and kept this advantage constant over time. For spring cereals, the yield gain increased over time since diversification adoption, arriving to a yearly surplus of c. 500 kg ha −1 after 50–60 years with still no sign of plateauing. Diversified rotations emerge as a promising way to adapt temperate cropping systems and contribute to food security under a changing climate. However, novel policies need to be implemented and investments made to give means and opportunities for farmers to adopt diversified crop rotations.